2014
DOI: 10.1007/s13679-014-0122-y
|View full text |Cite
|
Sign up to set email alerts
|

Food and Beverage Marketing to Youth

Abstract: After nearly a decade of concern over the role of food and beverage marketing to youth in the childhood obesity epidemic, American children and adolescents - especially those from communities of color - are still immersed in advertising and marketing environments that primarily promote unhealthy foods and beverages. Despite some positive steps, the evidence shows that the food and beverage industry self-regulation alone is not likely to significantly reduce marketing of unhealthy foods and beverages to youth. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 77 publications
0
12
0
Order By: Relevance
“…Most commonly, this content appears to be solicited through hashtag campaigns that encourage social media users to create and post branded content on social media. The public health literature, while offering extensive coverage of corporate advertising on social media, 11 14 and increasingly considering the public health relevance of UGC, 15 , 16 has yet to fully explore the intersections of corporate campaigns and UGC on social media. For example, a recent study of food advertising on Facebook by Freeman et al.…”
Section: Introductionmentioning
confidence: 99%
“…Most commonly, this content appears to be solicited through hashtag campaigns that encourage social media users to create and post branded content on social media. The public health literature, while offering extensive coverage of corporate advertising on social media, 11 14 and increasingly considering the public health relevance of UGC, 15 , 16 has yet to fully explore the intersections of corporate campaigns and UGC on social media. For example, a recent study of food advertising on Facebook by Freeman et al.…”
Section: Introductionmentioning
confidence: 99%
“…Marketing of foods and beverages that are unhealthy (i.e. high in saturated fat, sugar and/or sodium) to children and adolescents has received particular attention from researchers, public health advocates, and regulatory agencies as a probable contributor to the increased prevalence of childhood obesity (Federal Trade Commission, Centers for Disease Control and Prevention et al, 2011; Kraak, Story et al, 2011; Cheyne, Gonzalez et al, 2013; Powell, Schermbeck et al, 2011; Federal Trade Commission, 2012; Institute of Medicine, 2006; Center for Science in the Public Interest, 2010). Exposure to food-related television advertising is associated with children’s purchase requests, consumption patterns and adiposity (Chou, Rashad et al, 2008; Institute of Medicine, 2006; Andreyeva, Kelly et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…12 Despite these pledges, studies found marginal improvements in the overall marketing environment aimed at children, particularly nutritional content of marketed foods. 13-19 A 2010 White House Task Force on Childhood Obesity report and a 2012 IOM report noted this limited progress and the need for stronger standards to improve food marketing to children. 20,21 …”
Section: Introductionmentioning
confidence: 99%